Photovoltaic systems sizing using graphical user interface - Vega-Carranza, Kenneth (2019)
This paper shows a graphical interface implementation carried out using MATLAB to determine the size of the main components of a photovoltaic system. With this interface it is possible to select the main components in off-grid and on-grid systems. First, it is necessary calculate the photovoltaic array according to the energy demand and some conditions related to solar radiation and the system’s configuration. Then, for off-grid systems, it will be necessary to determine the size and array for the batteries. After that, it will possible to select solar controllers (for off grid systems) and inverters (for both kinds of systems). Finally, the graphical interface will show a summary table with the quantity of each component and its main electrical specs.